Strategi Komunikasi Sekretariat TKPSDA dalam Meningkatkan Kinerja TKPSDA Wilayah Sungai Toba-Asahan - Rini Novriani; Dewi Kurniawati; Iskandar Zulkarnain (MUKASI: Jurnal Ilmu Komunikasi, 2022)
The research aims to analyze the  communication strategy that is employed by the TKPSDA secretariat and analyze the dynamics and efforts in implementing the secretariat’s communication strategy in improving the performance TKPSDA Toba-Asahan River Area.  This research uses the concept of communicatrion strategy and Herbert Mead’s theory of symbolic interaction. The researcher uses a qualitative approach with a descriptive method. The research subjects consist of seven informants using the puposive technique. The results show that the communication  strategy of the TKPSDA secretariat is carried out by considering four aspects, namely the aspect of  knowing the communicant, the aspect of the message being conveyed, the aspect of the media being used, and the aspect of the communicator’s role. The obstacles faced by the TKPSDA secretariat are the different levels of members undesrstanding, the unvailability of facilities from members to carry out online activities, the  presence of TKPSDA  members representative of government elements, the factor of the work of the secretariat team that carries on the other works, and the monitoring and  evaluation have not been implemented towards recommendations of trial results oh the TKPSDA Toba-Asahan River Area.